2004
DOI: 10.1002/jssc.200401768
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a solid‐phase microextraction procedure for the determination of herbicides by micellar electrokinetic chromatography

Abstract: The use of a different optimization procedure that involves Experimental Design (ED) and Artificial Neural Networks (ANN) for the off-line coupling solid-phase microextraction-micellar electokinetic chomatography (SPME-MEKC) is presented. This combination of ED and ANN, mathematical tools not previously used in SPME-MEKC optimization, allowed us to obtain good extraction efficiencies in the SPME procedure for the determination of a group of eleven triazine herbicides in groundwater samples. Both extraction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…The combined use of SPE and online preconcentration strategies is shown to overcome the sensitivity problems usually linked to CE analysis of herbicides in environmental samples [80,83,84,115]. As an example, Hernández-Borges et al [115] reported the ultrasensitive determination of five herbicides in stagnant water by CE and UV detection combined with SPE and online preconcentration using stacking with matrix removal.…”
Section: Sample Preconcentrationmentioning
confidence: 98%
See 2 more Smart Citations
“…The combined use of SPE and online preconcentration strategies is shown to overcome the sensitivity problems usually linked to CE analysis of herbicides in environmental samples [80,83,84,115]. As an example, Hernández-Borges et al [115] reported the ultrasensitive determination of five herbicides in stagnant water by CE and UV detection combined with SPE and online preconcentration using stacking with matrix removal.…”
Section: Sample Preconcentrationmentioning
confidence: 98%
“…Among various CE modes utilized, MEKC was the most commonly used for determination of pesticides [78,79,89] and herbicides [37,38,81,83,84,[155][156][157][158]. SeguraCarretero et al [78] utilized MEKC with diode-array detector (DAD) for determination of imidacloprid and its metabolite 6-chloronicotinic acid in greenhouse air.…”
Section: Pesticides and Herbicidesmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated above, SPME prior to CE for pesticide analysis has only been used in three works [10][11][12]. SPME has several advantages over SPE or liquid-liquid extraction (e.g., faster, more simple, and environmentally friendly, etc.)…”
Section: Application Of Spme-rp-swmr-ce-uv To Real Samplesmentioning
confidence: 98%
“…Likewise, off-line preconcentration procedures based on solidphase microextraction (SPME) [10][11][12], SPE [13], or cloud point extraction (CPE) [14] have also been developed for being used with CE analysis. The use of these different preconcentration strategies prior to CE and their application to pesticide analysis has been recently reviewed by our group [15].…”
Section: Introductionmentioning
confidence: 99%